Sentralisasi administrasi keuangan Muawiyah bin Abi Sufyan: Inspirasi untuk manajemen fiskal modern (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
Muawiyah ibn Abi Sufyan, as one of the most influential leaders in the history of the Umayyad Caliphate, is known for his policies in managing state finances that have influenced the economic structure of the Islamic world. One of the main policies he implemented was the centralisation of financial administration, where Muawiyah centralised the management of taxes and supervision of state finances. This policy aimed to reduce abuse of power, and ensure a more equitable distribution of wealth. Although this policy was implemented in the 7th century, its relevance can be seen in the fiscal management of modern countries that face similar challenges, such as transparent and efficient tax management. This study aims to analyse Muawiyah bin Abi Sufyan’s economic policies, particularly in terms of financial centralisation and Baitul Mal management, and explore how the principles applied by him can still be adapted in the fiscal management of modern states. The article utilises a qualitative methodology and collects data through desk research. By tracking down, and accompanying scholarly sources of journals and books, evaluating, and documenting a variety of books that fit the topic of academic standards.
Keywords: Centralization; Economic Policy; Finance; Muawiyah bin Abi sufyan; Tax